Implementation of Environmental Issues in Teaching the Subject of Technical Education at Primary Schools - Ivana Tureková (International Journal of Engineering Pedagogy (iJEP), 2020)
Nowadays, environmental issues belong to frequently discussed topics. Our article focuses on the implementation of environmental issues in teaching the subject of Technical education at primary schools in the Slovak Republic. Our research sample consisted of 123 students, graduates of primary schools in Trnava, Trenčín and Bratislava regions after they started to study at secondary vocational schools. We wanted to find out more information about their experience related to working with tools, instruments and machines, to developing their creativity, designing and manufacturing of their hand-made products. Our main questions dealt with environmental issues and their acquisition in the subject of Technical education. Up to 55.5 % of respondents stated that they did not learn, or they did not remember the area of environmental issues within the given subject. 7.8 % of respondents remembered mainly the topic of waste sorting out of all environmental issues discussed at the lessons of Technical education. In general, environmental aspects as cross-cutting topics of the educational process can be adequately demonstrated and implemented in the subject of Technical education. However, this implementation also requires a new conceptual approach to the teachers` education and the lifelong education of the whole society, as well.